Anaesthetic Aproach Towards a Patient with Hurler Syndrom in the Magnetic Resonans Imaging Area (Annals of Medical Research, 2021)
None
Keywords: Hurler Syndrome, Anaesthesia, Magnetic Rezonans Imaging (MRI), Intubation Difficulties